Interpretation of in situ horizontal stress from self-boring pressuremeter tests in sands via cavity pressure less than limit pressure: a numerical study - Ahmadi, Mohammad Mehdi; Keshmiri, Ehsan (Environmental earth sciences, 2017)
The paper presents a numerical finite difference model of self-boring pressuremeter test (SBPM) using FLAC software. Different cavity expansion theories in sand have been compared to the results of numerical analyses carried out in this study. Limit pressure is believed to be used as a key parameter for the estimation of soil parameters from pressuremeter tests. In practice, SBPM tests are conducted up to 10–15% cavity strains, and the strain level associated with the limit pressure state is not reached. Therefore, determination of limit pressure usually needs extrapolation. In this paper, the authors suggest to use cavity pressure at 10% strain ( P 10 ) for the interpretation of in situ horizontal stress from SBPM test rather than limit pressure. For this purpose, more than 5000 numerical analyses of SBPM are carried out, and cavity pressures associated with 10% strain are deduced. Based on these extensive numbers of numerical analyses, a new relationship is established with the aid of genetic algorithm which correlates P 10 to soil parameters. The estimated values of P 10 from the proposed relationship are compared to a large database of measured ones obtained from laboratory and field results available in the literature. It was shown that the proposed relationship gives satisfactory predictions of P 10 . A chart was established for deduction of the in situ horizontal stress using the proposed relationship. This method can be used as a complement to liftoff method which is not reliable for estimation of the in situ horizontal stress when soil disturbance occurs at cavity wall.